Effects of Yacon Leaf Extract on MCP-1 and IL-10 Expressions and Macrophage Phenotypes in CKD Mouse Model - Sofyana, Meida; Wasityastuti, Widya; Ihsana, Nuni; Purwono, Setyo; Arfian, Nur (Faculty of Medicine, Universitas Padjadjaran, 2024)
Macrophages are essential in tissue homeostasis and immunity, but also contribute to disease development and progression. Chronic kidney disease (CKD) is characterized by interstitial infiltration of macrophages, the density of which correlates inversely with kidney survival. Studies have shown that yacon (Smallanthus sonchifolius) has beneficial effects on CKD. Therefore, this study aimed to investigate the effects of yacon leaf extract on mice with subtotal nephrectomy by evaluating the M1 and M2 macrophage counts and mRNA expressions of monocyte chemoattractant protein-1 (MCP-1 and IL-10. The mice were randomly divided into five groups: SO (negative control: underwent sham operation), SN (positive control: underwent subtotal nephrectomy), and yacon-treated groups: YK1, YK2, and YK3 (underwent subtotal nephrectomy, given peroral yacon leaf extract for 14 days with doses of 24,5 mg/kgBW/day, 49 mg/kgBW/day, and 98 mg/kgBW/day, respectively). The macrophage subtypes were assessed using immunohistochemistry anti-CD68 for M1 and anti-Arginase I for M2. MCP-1 and IL-10 mRNA expressions were analyzed using semi-quantitative PCR. Results showed that yacon leaf extract could significantly lower the M2 macrophage count (p<0.001) and the mRNA expressions of MCP-1 and IL-10 in all yacon-treated groups when compared to the SN group. However, the M1 macrophage count was only lower in the YK2 group (p=0.009). In conclusion, the administration of yacon leaf extract could attenuate kidney injury by lowering the macrophage count and the expression of MCP-1 and IL-10.